Peran Strategis Da’i Dalam Membangun Masyarakat dan Peradaban Islam di Desa Ngimbang - Ramadhani, Vella Octia; Al Samhah, Salwa Hanifiyyah; Ghofir, Jamal (ASWALALITA: Journal of Da'wah Management, 2025)
A dai holds an essential role in building an Islamic society that is obedient, ethical, and cultured. In carrying out the mission of dakwah, a dai not only conveys religious teachings in ritual form but also takes into account the social, cultural, political, and educational aspects of the community. Amidst the complex challenges of modern society, the role of the dai is expected to be more adaptive and relevant to contemporary needs. The question then arises: how can the role of a dai be maximized in creating a morally upright society and contributing to the development of an Islamic civilization that achieves excellence? In this context, the dai is not merely a religious messenger, but also a social transformation agent capable of instilling just and civilized character in individuals and society. This study uses a phenomenological approach with a qualitative method. This method is used to understand the meaning of the phenomenon of "The Strategic Role of Dai in Building Islamic Society and Civilization in Ngimbang Village", based on real symptoms that appear in the social life of the community. The phenomenological approach directs attention to the deep meaning of the presence of a da'i in the life of society, not just looking at his formal activities, but how his presence has a real influence on social change. Therefore, the continuous development of the capacity of da'i, both in terms of knowledge, spirituality, and communication skills, is an important need to realize a holistic, inclusive, and dynamic Islamic civilization.